CONSERVATISM, EDMUND BURKE, AND THE INVENTION OF A POLITICAL TRADITION, c. 1885–1914*. (29th October 2015) - Unknown
Abstract: This article addresses the reputation of Edmund Burke and his transformation into the 'founder of modern conservatism'. It argues that this process occurred primarily between 1885 and 1914 in Britain. In doing so, this article challenges the existing orthodoxy which attributes this development to the work of Peter Stanlis, Russell Kirk, and other conservative American scholars. Moreover, this article historicizes one aspect of the construction of C/conservatism as both an intellectual (small-c) and political (capital-C) tradition. Indeed, though the late Victorian and Edwardian period saw the construction of political traditions of an entirely novel kind, the search for 'New Conservatism' has been neglected by comparison with New Liberalism. Thus, this study explores three main themes: the impact of British debates about Irish Home Rule on Burke's reputation and status; the academic systematization of Burke's work into a 'political philosophy of conservatism'; and, finally, the appropriation of Burke by Conservative Unionists during the late Edwardian constitutional crisis. The result is to show that by 1914 Burke had been firmly established as a 'conservative' political thinker whose work was directly associated with British Conservatism.